Opto-elastic properties of FBG based fabryperot resonator: Fabrication, characterization, and applications / Md. Rajibul Islam - Md. Rajibul , Islam (2017)
Fiber Bragg Gratings (FBGs) are highly sensitive to acousto-optic wave, temperature, pressure wave, and etc. FBGs are used in our study to manufacture all fiber Fabry-Perot resonator (FPR) in different optical fibers. The variations in grating pitch and refractive index of the fiber device are the key contributors to its output spectral response and sensitivity. Opto-elastic properties of FPR play an important role in output spectral response. FBG based all-fiber FPR has been comprehensively studied in this thesis for effective, inexpensive and simple manufacture aspects. The background of FBGs, Fabry-Perot resonators, their fabrication procedures, applications, and operational principles are comprehensively discussed. Moreover, the background study on the widespread theory of opto-elasticity, the correlation of refractive index and stress, in silica based optical fiber is presented. In this thesis, the fabrication and characterization of FBG based short cavity FPR and PCF cavity FPR are demonstrated. In addition, opto-elastic properties of FBG based FPR in various fibers are studied under the influence of longitudinal waves, pressure and temperature through simulation and experimental investigation. Additionally, LP01-LP11 cross mode interference is observed in a single chirped grating (CG) inscribed in a two-mode fiber (TMF). Both spatial modes can be concurrently excited using a phase plate at different intensity ratio of LP01:LP11 in the TMF. Diverse interference patterns are formed in the output spectra by the excited input beams. These findings are significant steps in the advancement and characterization of more sophisticated grating structures on single mode and few mode optical fibers. This study will contribute to the understanding and designing of efficient FBG based Fabry- Perot resonators as well.